Pengembangan Media Pembelajaran E-Modul Menggunakan Sigil pada Kelas X RPL - Andriyas Hariyandi; Astri Indah Juwita; Tessya Maviza Sari (Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to determine the Effectiveness of E-Module Learning Media Using Sigil in Vocational Basics Subjects at SMKN 2 Padang. This research uses research & development method. The research subjects were 35 students. The research model used is the development research model (ADDIE) with the development steps as follows. (1) Analyze, (2) Design, (3) Development, (4) Implementation and (5) Evaluate. By obtaining the results of the validity test by the experts, the overall assessment of the validator test on the E-Module using Sigil in the Class X RPL Vocational Basics Subject at SMKN 2 Padang Odd Semester is 81.19%, it can be interpreted that Valid is used. The results of the practical test of 90.57%, can be interpreted as very practical to use. The results of the research on the effectiveness test of 87.31% can be interpreted as very effective in use. In conclusion, based on the assessment and input of experts as well as the results of the E-Modul field trial using Sigil as a learning medium, it has been tested for feasibility, excellence, and can be used in the learning process in the subjects of Vocational Basics class X RPL at SMKN 2 Padang.